Digestive Evaluation of Tofu Dregs Influence by Fermentation and Tannin - Zulkarnain, Zulkarnain; Sadarman, Sadarman; Prihambodo, Tri Rachmanto; Qomariyah, Novia; Laconi, Erika Budiarti; Jayanegara, Anuraga; Sofyan, Ahmad (Universitas Halu Oleo, 2022)
Tofu dregs are one of the high-protein feed ingredients and it is highly palatable for livestock, particularly ruminants. However, tofu dregs have the main disadvantage, i.e., they easily deteriorate due to their high water and protein contents. Fermentation of tofu dregs may be applied in order to prevent such deterioration. The aim of this experiment was to evaluate tofu dregs as influenced by fermentation and tannin extract from acacia bark on in vitro rumen fermentation and digestibility parameters. The experimental treatments were: NK (tofu dregs without fermentation and 0% tannin), NA (tofu dregs without fermentation and 2% tannin), FK (tofu dregs with fermentation and 0% tannin), and FA (tofu dregs with fermentation and 2% tannin). Data were analyzed by analysis of variance according to a randomized complete block design with four treatments and four replications. Results revealed tofu dregs with fermentation treatment have a significant increase (P<0.05) in gas production, and ammonia but do not affect other parameters such as propionic acid and butyric acid on fermentation products. Opposite to the rumen fermentation product, the tannin gives a significant effect (P<0.05) on all digestibility parameters so can be concluded tofu dregs with fermentation and tannin approaches affect to rumen fermentation product and tannin has a weaker effect than fermentation even though 20 g/kg addition decrease digestibility of rumen in vitro.Keywords: ruminal fermentation product, silage, tannin, tofu dregs